Analisis Implementasi Kebijakan Pemberian Bantuan Beasiswa Kedokteran di Kabupaten Bolaang Mongondow Selatan - Manggopa, Fitria Yunita; Sakir, Moch; Rahmisyari (Melati Institute, 2024)
This research aims to analyze the implementation of the policy of providing medical scholarships in South Bolaang Mongondow Regency with a focus on policy objectives, with the research results showing that a thorough evaluation of success indicators is needed to ensure that the objectives of this policy are achieved effectively, in addition to human and financial resources as well. plays an important role where budget limitations and human resource capacity have an impact on program sustainability. The success of policy implementation is greatly influenced by the characteristics of the implementing organization which has good structure and coordination, as well as the attitude of implementers who support the policy. However, the lack of effective communication between organizations and the impact of social, economic and political conditions are significant obstacles in implementing this policy.